Terpenoid natural products exert neuroprotection via the PI3K/Akt pathway - Xu, Bingyao; Bai, Lan; Chen, Lu; Tong, Rongsheng; Feng, Yibin; Shi, Jianyou (Frontiers in Pharmacology, 2022)
PI3K/Akt, an essential signaling pathway widely present in cells, has been shown to be relevant to neurological disorders. As an important class of natural products, terpenoids have large numbers and diverse backbones, so they have a great chance to be identified as neuroprotective agents. In this review, we described and summarized recent research for a range of terpenoid natural products associated with the PI3K/Akt pathway by classifying their basic chemical structures of the terpenes, identified by electronic searches on PubMed, Web of Science for research, Google Scholar et al. websites. Only articles published in English were included. Our discussion here concerned 16 natural terpenoids and their mechanisms of action, the associated diseases, and the methods of experimentation used. We also reviewed the discovery of their chemical structures and their derivatives, and some compounds have been concluded for their structure-activity relationships (SAR). As a result, terpenoids are excellent candidates for research as natural neuroprotective agents, and our content will provide a stepping stone for further research into these natural products. It may be possible for more terpenoids to serve as neuroprotective agents in the future.